RELEVANT FACTORS IN SEXUAL INITIATION: ADOLESCENTS’ COLLECTIVE SPEECH IN A SCHOOL FROM THE CITY OF RECIFE, BRAZIL - Silva, Vilma Maria (2018)
In adolescence sexuality has special meaning, since the individual begins the consolidation of the sexualidentity and reaches the reproductive capacity. The first sexual intercourse happens sooner and the healthy experience of the period of experimentation inherent in adolescence will contribute to the formation of adults capable of making conscious and planned decisions throughout life, avoiding traumatic situations. This qualitative-quantitative research is the result of a dissertation aiming to know the adolescents’ opinions of a public school with regard to relevants factors to sexual initiation. The population was constituted by teenagers between 15 and 19 years old and the sample was composed of 61 youngsters. It was used the collective subject speech’s technique with the support of Qualiquantisoftware. The identified categories were: preventive practices; feelings e partnership; financial, familiar and personal structure; support network; juvenile prominence and female gender: responsibility, lack of knowledge and submission. Although this matter is much discussed, many adolescents don’t bring the information to their life contexts. It is recommended that families and the schools prioritize spaces for discussion of this subject, besides the access to sexual and reproductive.